Age-specific prevalence of diagnosed systemic lupus erythematosus in Germany 2002 and projection to 2030. (November 2014) - Brinks, R; Fischer-Betz, R; Sander, O; Richter, J G; Chehab, G; Schneider, M
Objective: The objective of this report is to estimate the prevalence and future number of cases of systemic lupus erythematosus (SLE) in Germany. Methods: Data from a representative sample of all insurants from the statutory health insurance in Germany comprising more than 2.3 million individuals have been screened for SLE diagnoses. The gender- and age-specific prevalence of SLE is calculated. The case definition is based on at least one recorded diagnosis of SLE during 2002. The stratum-specific prevalence is applied to the current and the future population of Germany in order to estimate and predict the number of people with SLE until 2030. Results: The overall prevalence of diagnosed SLE in 2002 was 15.4 (95% CI: 13.1–17.9) and 55.4 (51.4, 59.8) per 100, 000 in the male and female German population. This corresponds to an estimated 30, 000 and 31, 000 people with diagnosed SLE in 2002 and 2010, respectively. This number will slightly increase until 2020 and decrease thereafter. Conclusions: Compared with health insurance data from France, the prevalence in our data is similar. Under the assumption that the gender- and age-specific prevalence of SLE in Germany will not change considerably, the number of cases in the next two decades will change only slightly.